Inconclusive results of slow cortical potential neurofeedback for the treatment of chronic post-stroke attention deficits - Kleih, Sonja C.; Botrel, Loic (Frontiers in Human Neuroscience, 2024)
Individuals who have suffered a stroke may experience long-lasting cognitive impairments that can worsen if left untreated. We investigated whether voluntary control of slow cortical potentials (SCP) through neurofeedback would help alleviate chronic post-stroke symptoms of impaired attention. The study initially enrolled twenty-eight participants, but due to a high dropout rate, only sixteen participants completed eight SCP neurofeedback training sessions within three to four weeks. During these sessions, we gave feedback to the participants on their ability to regulate SCPs on a computer screen. Our findings showed a non-significant increase in SCP regulation towards cortical negativity. On the behavioral level, we found improved test values in the divided attention and attentional flexibility subtests of the test battery for attention performance. However, we cannot eliminate the possibility that nonspecific effects influenced or caused our results. We have not observed any improvement regarding attention deficit symptoms in the individual's daily life. We identified five individuals who could gain SCP control successfully and consistently towards negativity. In this group of responders, we observed an improvement in the test results related to divided attention but no other attentionrelated improvements. Based on our observations, evidence for the effectiveness of SCP neurofeedback training in addressing attention deficits after a stroke is inconclusive. More research is necessary to determine its effectiveness in helping stroke survivors cope with attention-related challenges in their daily lives.